PENGARUH KOMBINASI DOSIS PUPUK UREA, TSP, KCL TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN KACANG HIJAU (Vigna radiata L.) - Riky Geissler Wally (Bajang Institute, 2025)
This research aims to determine the different combinations of urea, TSP, and KCL fertilizers on the growth and production of mung bean plants. This study was conducted using a randomized block design (RBD) consisting of one factor, namely the application of urea, TSP, and KCL fertilizers with 5 treatment levels; K0 = without fertilizer, K1 = 15 grams/plant, K2 = 10 grams/plant, K3 = 15 grams/plant, and K4 = 20 grams/plant. Each treatment was repeated four (4) times. The results showed that the combination of urea, TSP, and KCL fertilizer doses did not have a significant effect on the variables of plant height, leaf length, leaf width, pod length, number of pods, and dry seed weight, except for the number of leaves and the highest stem diameter which were produced at the treatment dose of 5 grams/plant